Building strategic relationships : how to extend your organization's reach through partnerships, alliances, and joint ventures - 187671 Bergquist, William H.; Betwee, Juli; Meuel, David (San Francisco : Jossey-Bass Pub., 1995)
Includes bibliographical references and index.